Economic Benefits and Energy Efficiency of Using Solar Panels Energy for Paddle Aerators in Shrimp Ponds (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
Solar energy is a new innovation in aquaculture. The purpose of this study was to determine the economic benefits and energy efficiency of using solar panel energy on paddle aerator machines in shrimp ponds. The research method employed was a causal ex-post facto design. The variables observed were the electricity consumption of paddle aerators using solar energy compared to those using conventional energy sources. The research findings indicate that the oxygen production rates of paddle aerators were 2.04-2.77 mgO2/hour (solar panel) and 2.02-2.89 mgO2/hour (non-solar panel). Solar panels generated electrical energy in paddle aerators at rates of 8.34-8.75 watts. Electricity consumption by paddle aerators was recorded at 7.10-8.65 kW (solar panel) and 6.89-9.28 kW (non-solar panel). Quantitatively, the efficiency of electricity was found to be 0.10-1.24 watts when using solar panels. The use of solar panels is also considered more cost-effective for operational costs in intensive shrimp farming. Conclusion, the use of solar energy via solar panels for paddle aerators proves highly effective and economical compared to conventional electricity sources. Additionally, this system supports the operational effectiveness of the equipment throughout its technical lifespan.